2022
DOI: 10.4067/s0718-221x2023000100402
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the influence of radiata pine log variables on structural lumber production

Abstract: We run logit models to explain the variability of Pinus radiata structural lumber in 71 second and third unpruned logs. The response variable was the proportion of lumber with a static modulus of elasticity greater or equal than 8000 MPa, pMSG8+, and the explanatory variables were log volume, branch index, largest branch, log internode index, wood basic density, and acoustic velocity. The average pMSG8+ volume was 44,30 % and 36,18 % in the second and third log respectively. Ten models were selected based on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The value of improving corewood quality in radiata pine affects decision-making on stocking, early and intermediate silviculture, and has a strategic impact on economic returns and rotation age. As an example, Gavilán et al (2023) showed that an average increase of 1% in corewood acoustic velocity implies an average increase of structural wood in a log between 8-9% for second and third logs.…”
Section: Discussionmentioning
confidence: 99%
“…The value of improving corewood quality in radiata pine affects decision-making on stocking, early and intermediate silviculture, and has a strategic impact on economic returns and rotation age. As an example, Gavilán et al (2023) showed that an average increase of 1% in corewood acoustic velocity implies an average increase of structural wood in a log between 8-9% for second and third logs.…”
Section: Discussionmentioning
confidence: 99%